The Implementation of the Muhawarah Method in Improving Arabic Speaking Skills at MA NW Dasan Lian - Hamzani (Journal of Education, Teaching, and Learning, 2025)
This study aims to improve Arabic speaking skills among students at MA NW Dasan Lian through the implementation of the Muhawarah (dialogue) method. The problem addressed in this research was the students’ low proficiency in speaking Arabic, characterized by limited vocabulary, lack of fluency, and low confidence, primarily due to monotonous teaching methods and minimal speaking practice. The research was conducted using a Classroom Action Research (CAR) design, based on the Kemmis and McTaggart model, which consists of four stages: planning, acting, observing, and reflecting. The study was carried out in two cycles, with each cycle involving three meetings. Data collection methods included classroom observation, pre-tests and post-tests, and documentation. In Cycle I, students showed moderate improvement, with an average pre-test score of 67 and a post-test score of 78. However, many students remained in the "Fair" or "Poor" categories. Adjustments were made in Cycle II, including more interactive teaching, the use of audio materials, and motivational strategies. This resulted in a significant improvement in students’ speaking skills. In Cycle II, the average pre-test score increased to 82 and the post-test score to 83, with most students achieving a "Good" category. The findings demonstrate that the Muhawarah method significantly enhances students’ fluency, confidence, and participation in Arabic language learning. These results support previous studies on dialog-based instruction and highlight the method’s relevance in secondary Islamic educational settings. The study concludes that structured dialogue is a practical and effective approach to Arabic instruction at the secondary level.